Short-lived climate pollutant mitigation and the Sustainable Development Goals. Issue 12 (December 2017) - Haines, Andy; Amann, Markus; Borgford-Parnell, Nathan; Leonard, Sunday; Kuylenstierna, Johan; Shindell, Drew
Abstract The post-2015 development agenda is dominated by a set of Sustainable Development Goals (SDGs) that arose from the 2012 Rio+20 United Nations Conference on Sustainable Development. The 17 goals and 169 targets address diverse and intersecting aspects of human and environmental needs and challenges. Achieving the SDGs by 2030 requires implementing coordinated and concerted strategies and actions that minimize potential trade-offs and conflicts and maximize synergies to contribute to multiple SDGs. Measures to mitigate emissions of short-lived climate pollutants are an example of actions that contribute to multiple outcomes relevant to development. This Perspective highlights the interlinkages between these pollutants and the SDGs, and shows that implementing emissions reduction measures can contribute to achieving many of the SDGs. Many of the measures required to reduce emissions of short-lived climate pollutants contribute to achieving the sustainable development goals while complementing decarbonization efforts required to reduce long-term climate change.